Kemampuan Good Corporate Governance Memoderasi Pengaruh Nilai Perusahaan pada Praktik Perataan - Permanasari, Ni Made Dwi; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p07, 2018)
Firm value was the factor for management to become opportunistic by doing income smoothing. This research has a purpose to giving an empirical proof about the ability of good corporate governance in moderating the relation between firm value and income smoothing. The number of sample on 2012-2016 period in property and real estate sector was about 160 observations. This study applying non probability with purposive sampling technique. The process of analysis data was through factor analysis and logistic regression with MRA .  There were two main result of this research included: 1) firm value negatively influence on income smoothing but not significantly; 2) good corporate governance did not weaken the relation of firm value and income smoothing. Keywords:   firm value, income smoothing, and good corporate governance